APLIKASI TOUR WISATA PAGAR ALAM - Susanti, Tri; Sasmita, Sasmita (Jurnal Teknologi Informasi Mura, 2023)
This research aims to create a tour application for the natural fence tourist attraction. Currently, there is no tour application that manages tourist attractions in Pagar Alam City and providing information about tourist attractions is still done via social media so that sometimes tourists only know a little information about tourist attractions in Pagar Alam City and some tourists are confused when they arrive. to Pagar Alam City be- cause they don't know about nearby accommodation or good locations for tourist attractions. Of course, this is not optimal in attracting tourists to visit tourist attractions. The system development method used is the System Development Life Cycle (SDLC) include system analysis, system design, system development and testing, system implementation, operation and maintenance, system evaluation. therefore we need a "Pagar Alam Tourist Attraction Application" which is able to contain a lot of information about tourist attractions, rates, accommodation and tour packages.